Medico-legal significance of service difficulties and clinical errors in the management of patients with inflammatory bowel diseases. (March 2015) - Farrukh, Affifa; Mayberry, John F
There is a significant growth in medical litigation, and cases involving the care and management of patients with inflammatory bowel disease are becoming common. There is no central register of such cases, and the majority are settled before court proceedings. As a result, there is no specific case law related to such conditions, and secrecy usually surrounds the outcome with "no admission of guilt" by the defendant and a clause about non-disclosure and discussion linked to the financial compensation received by the claimant. This review discusses common areas of potential litigation.